Bladder cancer therapy without toxicity—A dose‐escalation study of alpha1‐oleate. Issue 9 (11th May 2020) - Hien, Tran Thi; Ambite, Ines; Butler, Daniel; Wan, Murphy Lam Yim; Tran, Tuan Hiep; Höglund, Urban; Babjuk, Marek; Svanborg, Catharina
Abstract: Potent chemotherapeutic agents are required to counteract the aggressive behavior of cancer cells and patients often experience severe side effects, due to tissue toxicity. Our study addresses if a better balance between efficacy and toxicity can be attained using the tumoricidal complex alpha1‐oleate, formed by a synthetic, alpha‐helical peptide comprising the N‐terminal 39 amino acids of alpha‐lactalbumin and the fatty acid oleic acid. Bladder cancer was established, by intravesical instillation of MB49 cells on day 0 and the treatment group received five instillations of alpha1‐oleate (1.7‐17 mM) on days 3 to 11. A dose‐dependent reduction in tumor size, bladder size and bladder weight was recorded in the alpha1‐oleate treated group, compared to sham‐treated mice. Tumor markers Ki‐67, Cyclin D1 and VEGF were inhibited in a dose‐dependent manner, as was the expression of cancer‐related genes. Remarkably, toxicity for healthy tissue was not detected in alpha1‐oleate‐treated, tumor‐bearing mice or healthy mice or rabbits, challenged with increasing doses of the active complex. The results define a dose‐dependent therapeutic effect of alpha1‐oleate in a murine bladder cancer model. Abstract : What's new? Tumor resection is a standard treatment for bladder cancer and often is followed by adjuvant intravesicle chemotherapy or immunotherapy. These treatments, however, frequently are accompanied by significant side effects. Here, the authors explore the effects of the peptide‐fatty acid complex alpha1‐oleate, previously reported to possess tumoricidal activity and a promising agent for the treatment of non‐muscle invasive bladder cancer. Compared to untreated mice, animals treated with alpha1‐oleate experienced a dose‐dependent reduction in tumor size, without evidence of local or systemic toxicity. The findings provide essential background for clinical trials examining the effects of alpha1‐oleate in humans.